Tingkat Kebugaran Jasmani Siswa Sekolah Dasar Negeri 1 Karangpoh - Mokhamad Parmadi; Fajar Maulana Rahman (Mathematics Education Study Program, 2025)
This study aims to determine the level of physical fitness of male and female students of SD Negeri 1 Karangpoh. This study is a quantitative descriptive study with a presentation of the percentage of the level of physical fitness which will later be expressed is described in terms of the physical condition (VO2Max) of students of SD Negeri 1 Karangpoh. The sampling technique used total sampling, with 40 students participating. The instrument used in this study was the bleep test. The data analysis technique used descriptive analysis in the implementation of the sports measurement test that measured the VO2Max level of students of SD Negeri 1 Karangpoh. From the results of the study and discussion, it can be concluded that the results of the bleep test indicate that the level of endurance possessed by students as a whole still has a rating that is included in the category of less. can be seen from the results obtained having the lowest result of 20.8 and the highest value in this test is 44.5. From these findings, it is necessary to carry out follow-up to improve students' physical fitness, which is expected to improve physical fitness can encourage students to be even better in the learning process.